Prenatal anesthetic exposure and offspring neurodevelopmental outcomes—A narrative review - Zhou, Nannan; Liang, Shuang; Yue, Xinying; Zou, Wangyuan (Frontiers in Neurology, 2023)
While it is common for pregnant women to take anesthesia during surgery, the effects of prenatal anesthesia exposure (PAE) on the long-term neurodevelopment of the offspring remain to be clarified. Preclinical animal research has shown that in utero anesthetic exposure causes neurotoxicity in newborns, which is mainly characterized by histomorphological changes and altered learning and memory abilities. Regional birth cohort studies that are based on databases are currently the most convenient and popular types of clinical studies. Specialized questionnaires and scales are usually employed in these studies for the screening and diagnosis of neurodevelopmental disorders in the offspring. The time intervals between the intrauterine exposure and the onset of developmental outcomes often vary over several years and accommodate a large number of confounding factors, which have an even greater impact on the neurodevelopment of the offspring than prenatal anesthesia itself. This narrative review summarized the progress in prenatal anesthetic exposure and neurodevelopmental outcomes in the offspring from animal experimental research and clinical studies and provided a brief introduction to assess the neurodevelopment in children and potential confounding factors.